2013
DOI: 10.1093/nar/gks1461
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative recruitment of HMGB1 during V(D)J recombination through interactions with RAG1 and DNA

Abstract: During V(D)J recombination, recombination activating gene (RAG)1 and RAG2 bind and cleave recombination signal sequences (RSSs), aided by the ubiquitous DNA-binding/-bending proteins high-mobility group box protein (HMGB)1 or HMGB2. HMGB1/2 play a critical, although poorly understood, role in vitro in the assembly of functional RAG–RSS complexes, into which HMGB1/2 stably incorporate. The mechanism of HMGB1/2 recruitment is unknown, although an interaction with RAG1 has been suggested. Here, we report data dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 74 publications
0
33
0
Order By: Relevance
“…Following DNA cleavage by RAG, the nicked strand is converted to a hairpin and then the broken ends are joined by several proteins involved in DNA damage responses (Gellert, 2002). HMGB1 plays an essential role in V(D)J recombination by formation of RAG-RSS-HMG complexes to enhance RAG1/RAG2 activity (Agrawal and Schatz, 1997; Dai et al, 2005; Grundy et al, 2009; Little et al, 2013; Swanson, 2002a, b). The knowledge of their interconnection is essential for our understanding of immune cell development.…”
Section: Hmgb1 Functionmentioning
confidence: 99%
“…Following DNA cleavage by RAG, the nicked strand is converted to a hairpin and then the broken ends are joined by several proteins involved in DNA damage responses (Gellert, 2002). HMGB1 plays an essential role in V(D)J recombination by formation of RAG-RSS-HMG complexes to enhance RAG1/RAG2 activity (Agrawal and Schatz, 1997; Dai et al, 2005; Grundy et al, 2009; Little et al, 2013; Swanson, 2002a, b). The knowledge of their interconnection is essential for our understanding of immune cell development.…”
Section: Hmgb1 Functionmentioning
confidence: 99%
“…Swanson [162] further demonstrated that recombinant mammalian HMGB1 binds to the 12/23 substrates in vitro, and that it does so in a complex with the RAG1 and 2 proteins, again mimicking the early steps in the recombination process. More recent experiments have suggested that HMGB1 is initially recruited to a complex of RAG proteins plus DNA to form a tertiary complex that is stable throughout the recombination process [213]. Aidinis et al [214] were among the first to propose that RAG proteins recruit HMG1 and HMG2 to facilitate recombination signal sequence binding and to enhance the intrinsic DNA-bending activity of RAG1 and RAG2 proteins.…”
Section: Double-strand Break Repairmentioning
confidence: 99%
“…Interestingly, HMGB1 can both maintain and produce EDSBs. HMGB1 is a known protein that plays a role in maintaining EDSBs generated by the V(D)J recombination process (22)(23)(24) and possesses deoxyribose phosphate lyase activity (25). RIND-EDSBs are located in specific genomic regions, that is, their occurrences are nonrandom.…”
mentioning
confidence: 99%